1992
DOI: 10.1128/jb.174.1.35-39.1992
|View full text |Cite
|
Sign up to set email alerts
|

New minC mutations suggest different interactions of the same region of division inhibitor MinC with proteins specific for minD and dicB coinhibition pathways

Abstract: Proper positioning of division sites in Escherichia coli requires balanced expression of minC, minD, and minE gene products. Previous genetic analysis has shown that either MinD or an apparently unrelated protein, DicB, cooperates with MinC to inhibit division. We have isolated and sequenced minC mutations that suppress division inhibition caused by overproduction of either DicB or MinD proteins. Most missense mutations were located in the amino acid 160 to 200 region of MinC (231 amino acids). Some mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…1, SB, and 6). The product of the putative B. subtilis minC gene is similar to E. coli MinC in a region that is thought to be responsible for interactions with the E. coli cell division proteins MinD and DicB (26). In agreement with the view that the B. subtilis minC-and minD-like genes are involved with septum placement, this DNA is the site of the divlVBl minicell mutation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…1, SB, and 6). The product of the putative B. subtilis minC gene is similar to E. coli MinC in a region that is thought to be responsible for interactions with the E. coli cell division proteins MinD and DicB (26). In agreement with the view that the B. subtilis minC-and minD-like genes are involved with septum placement, this DNA is the site of the divlVBl minicell mutation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…One expectation of this hypothesis is that the region of MinC which interacts with MinD should be more conserved than the rest of the molecule. Mulder et al (30) recently identified a series of mutations within minC which suppress division inhibition induced by overexpression of minD. Significantly, these mutations cluster within the conserved region of MinC.…”
Section: Discussionmentioning
confidence: 99%
“…The specific glycine substitutions selected in the present study were based on previous reports in which minC Ec mutants were characterized after mutagenesis with nitrosoguanidine (12), ethyl methanesulfonate (18), or hydroxylamine (22). While many induced MinC Ec mutants had nonsense and missense mutations, several mutations involved changes from glycine (G) to charged amino acids, such aspartic acid (G10D and G171D), glutamic acid (G161E), lysine (G161K), and arginine (G176R) (18,22). In the present study, mutations at nonconserved (i.e., neutral) C-terminal residues (E144I mutation in MinC Ng and P141A mutation in MinC Ec ) were also created to validate the functional significance of mutations in conserved glycine residues of MinC.…”
Section: Resultsmentioning
confidence: 99%
“…Lutkenhaus and Sundaramoorthy (21) recently proposed that the interaction between MinC and MinD probably occurs in the cytoplasm and that the MinD-ATP-MinC complex persists because MinC does not stimulate the ATPase activity of MinD. Several spontaneous MinC Ec C-terminal mutants, including MinC Ec G161E, G171D, and G171S, have been isolated and analyzed to determine their morphological effects when they are expressed in E. coli (14,18,22,26). However, these chromosomal mutants were not tested for functionality by overexpression in E. coli or by yeast two-hybrid analyses.…”
Section: Discussionmentioning
confidence: 99%